Analisis Determinan Intelectual Capital Disclosure Pada Perusahaan Real Estate dan Property di Indonesia - Bela Nanda Sari; Debbi Chyntia Ovami (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to analyze the effect of firm size, firm age, profitability, leverage, and independent commissioners on intellectual capital disclosure. This study uses a sample of real estate and property companies listed on the Indonesia Stock Exchange in 2018-2020 with a population of 60 companies and a total sample of 12 companies. This study used purposive sampling method as a data collection method. This study uses panel data regression analysis with the Eviews version 10 program. The results of this study indicate a positive and significant effect on intellectual capital disclosure. While, company size, company age, and independent commissioners have a negative and insignificant effect on intellectual capital disclosure. Profitability has a positive and not significant effect. Simultaneously, this study shows that firm size, firm age, profitability, leverage, and independent commissioners of intellectual capital disclosure.